Discovery of a highly magnetic He-sdO star from a double-degenerate binary merger - Dorsch, Matti; Reindl, N.; Pelisoli, I.; Heber, Ulrich; Geier, S.; Istrate, A. G.; Justham, S. (Astronomy & Astrophysics, 2022)
Helium-rich hot subdwarf stars of spectral type O (He-sdO) are considered prime candidates for stellar merger remnants. Such events should lead to the generation of strong magnetic fields. However, no magnetic He-sdO has yet been unambiguously discovered despite the high magnetic rate (20%) among white dwarf stars, the progeny of hot subdwarfs. Here we present the discovery of a strong magnetic field (B = 353 ± 10 kG) from Zeeman-split hydrogen, helium, and metal lines in the optical X-shooter spectrum of an He-sdO and present the first spectroscopic analysis of any magnetic hot subdwarf. For this we used line-blanketed TLUSTY non-local thermodynamic equilibrium models and assumed a simple homogeneous magnetic field. The derived atmospheric parameters Teff = 44 900 ± 1000 K and log g = 5.93 ± 0.15 are typical for He-sdO stars, while the star is less hydrogen-poor than most He-sdOs at log n(He)/n(H) = + 0.28 ± 0.10. The star is a slow rotator (vrot sin i < 40 km s-1). Its chemical composition is N-rich and C- and O-poor, and the Si and S abundances are close to solar. Combining the atmospheric parameters with Gaia parallax and photometry, the stellar radius and luminosity are found to be typical for He-sdOs and place the star on the helium main sequence in the Hertzsprung-Russell diagram. Its mass of 0.93-0.30+0.44 M⊙, although uncertain, appears to be remarkably high. The strong magnetic field along with the atmospheric parameters and metal abundances provide overwhelming evidence for the double-degenerate merger scenario.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Stars: early-type; Stars: magnetic field; Subdwarfs